Application of long-distance directional drilling gas drainage technology inQinglong Coal Mine - XUE Haiteng; LI Xijian; LIANG Daofu; CHEN Liuyu; MA Shengxiang (Gong-kuang zidonghua, 2020)
The coal mines in Guizhou Province have complex geological structures, high gas content, and soft coal seams, making gas management difficult. In order to improve gas management level in the area, at the range of 5-205 m forward from Y3 point of the transportation roadway of 21601 working face in Qinglong Coal Mine, the kilometer drilling rig is used for field application of gas drainage technology of long-distance directional drilling along layer. The directional drilling technology and branch drillings control technology are used to ensure drilling trajectory control accuracy and avoid blind drilling and blind pumping. The application results show that the desorbable gas from two coal samples are 1.772 9, 2.191 3 m3/t, and the residual gas content is 4.773 9, 5.170 4 m3/t, both are less than 8 m3/t, which meet the basic gas drainage requirements of mine. The average gas drainage volume reached 1.26 m3/min, which is 12% higher than the original value. Compared with conventional drilling, volume fraction of the gas extracted by directional drilling increased by 50%, and the gas treatment effect is significant.